School subsidies for the poor: evaluating a Mexican strategy for reducing poverty -- PROGRESA in Mexico - Schultz, T. Paul (International Food Policy Research Institute, 2001)
This paper assesses how the Programa Nacional de Educacion, Salud, y Alimentacion (PROGRESA) program has affected the school enrollment of Mexican youth in the first 15 months of its operation. PROGRESA provides poor mothers in poor rural communities with education grants, if their children attend school regularly. Enrollment rates are compared between groups of poor children who reside in communities randomly selected to participate in the initial phase of the PROGRESA program and those who reside in other comparably poor (control) communities. Pre-program comparisons document how well the randomized design is implemented, and double-differenced estimators are reported over time within this panel of children. Probit models are then estimated for the probability that an individual child is enrolled, which statistically controls for additional characteristics of the child, their parents, local schools, and community, and for samples of different compositions, to evaluate the sensitivity of the estimated program effects to these variations. If the current relationship of the program outlays to enrollments, and that of schooling to increased adult earnings, both persist in the future, the internal rate of return to the PROGRESA educational grants as an investment is estimated to be about 8 percent, which accrues in addition to the program’s efficacy as a poverty reduction program.